Genetic characterisation for Yan'an Han population in Northern Shaanxi Province, China, via 38Y-STRs using Yfiler™ Platinum - Luyao Li; Lilan Yao; Huilin Gong; Li Luo; Hau Liang; Jiaojiao Zhang; Yuanyuan Wang; Guanglin He; Fuquan Jia; Pengyu Chen (Taylor & Francis Group, 2021)
Background Haplotype/allele frequency data of Y-chromosomal STR loci in ethnically diverse populations are essential for forensics, anthropology and genealogy. However, genetic structure and forensic characterisation of the Chinese Han population residing in Yan'an, in the Northern Shaanxi Province, remain unclear. Aim To assess forensic efficiency for 38 Y-Chromosomal STR loci in Yan'an Han population and reveal the population genetic relationships between Yan'an Han and other populations at a nationwide and worldwide level. Subjects and methods 719 healthy unrelated males were genotyped using the Yfiler™ Platinum system. Haplotype/allele frequencies and forensic parameters were calculated. Multi-dimensional scaling plots (MDS) and neighbor-joining (N-J) tree were used to explore the population structure based on the pairwise gene distances (Rst). Results A total of 707 haplotypes were identified, among which 697 unique haplotypes were observed (98.59%). The overall haplotype diversity (HD) and discrimination capacity (DC) were 0.9999 and 0.9833, respectively. Comprehensive population comparisons showed Yan'an Han is genetically closer to linguistically similar populations in China, and more related to East Asian populations around the world. Conclusion The present results give a unique insight into the Yan'an Han population via the set of 38 Y-STRs, which can be used for forensic practice and human genetics research.